Metabolic Changes during Differentiation in Callus Cultures of Stevia rebaudiana (Bertoni) - Kumari; Renu, Narender Singh*, Kuldeep Yadav, Suman (Journal of Phytology, 2011)
Stevia rebaudiana (Bertoni) is an economically important medicinal plants act as an option for artificial sweetening agents. The plant regeneration protocol under in vitro conditions has been developed for this natural sweetener herb. Callus was efficiently induced when leaf segments were cultured on MS medium supplemented with 1.0 mg/l 2, 4-D + 1.0 mg/l Kinetin. The above callus was sub cultured on MS medium + 0.5 mg/l BAP + 0.3 mg/l NAA for root differentiation and on MS medium + 0.5 mg/l BAP + 0.1 mg/l NAA for shoot differentiation. Biochemical changes occurring during the callus differentiation were adopted to quantify the metabolites. Metabolites like starch, total soluble sugars and total phenols decreased while total soluble proteins increased in callus culture during the process of root and shoot differentiation. Key words: Callus, differentiation, in vitro, metabolites, Stevia rebaudiana Abbreviations:Ã‚Â BAP Benzyl amino purine; 2,4-D 2,4-Dichlorophenoxyacetic acid; MS Murashige and Skoog (1962) basal medium; NAA ÃŽÂ±-naphthalene acetic acid; IBA Indole-3-butyric acid; IAA Indole acetic acid <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Narender Singh et al. Metabolic Changes during Differentiation in Callus Cultures of Stevia rebaudiana (Bertoni). J Phytol 3/3 (2011) 63-67.